The political ecology of tropical forests in Southeast Asia: historical roots of modern problems - Jong, W. de; Tuk-Po, L.; Ken-Ichi, Abe (Kyoto University Press, 2003)
A simplistic explanation of why tropical forests degrade or disappear all together is, because loggers take out too many trees, companies convert forest for plantations, and small farmers slash forest to make agricultural fields. Political ecology is a scientific inter-discipline that tries to identify the political dimension of forest resource appropriation, contestation over forest benefits, and the role of power and discourse in the processes of unsustainable use and resulting forest degradation. This chapter summarizes ten chapters in the volume in which it is published. Several of chapters demonstrate that modern struggles over forests have their roots in colonial periods. Colonial powers used force, but also the argument that deforestation negatively affected the local climate, to expulse forest farmers from timber rich forest lands. Often control of the trade of lucrative forest products like rattan was decided by force. In these struggles, colonial powers used force against local Sultans, local Sultans used force against forest dwellers, and powerful forest dweller groups used force against weaker groups.